The matter of practice : exploring new materialisms in the research and teaching of languages and literacies - Porter, Curt; Griffo, Rachel (Research in second language learning., 2021)
"The Matter of Practice presents work by teacher-scholars from around the world who are rethinking the relationship between matter and meaning. By emphasizing spatial, bodily, and sensual dimensions of language and literacy practices, this volume offers a portrait of language pedagogy and research that challenges traditional barriers between subjects and objects, speech and noise, and languages and things. We envision the term 'new materialisms' as an invitation to locate theorizing, researching, and teaching practices within the rhythms and textures of our material, sensory, and perceptual lives. These chapters enact a hope that increased engagement with our physical surroundings and sensory experiences can extend the sphere of our social, creative, and intellectual labor and expand our understanding of what 'counts' as meaningful action"--